Leadership and organizations - Bryman, Alan (Routledge library editions. Organizations : theory & behaviour ;, 2013)
In this textbook Alan Bryman provides a detailed and critical examination of the literature on leadership in organizations, giving special recognition to the needs of students of organizational behaviour and the social psychology of organizations. After an examination of the complexity of the concept of leadership, the author describes the major approaches to the analysis of leadership in organizations, including: the idea that effective leaders have special traits; the various attempts to examine leader behaviour; normative approaches to the study of leadership; and the various theories which emphasize the importance of recognizing situational differences in understanding leadership effectiveness.